The Role of Teamwork in Building Patient Safety Culture at Hospital “X” in South Jakarta, Indonesia - Shameela, Alika; Sulistiadi, Wahyu (Alta Dharma Publisher, 2024)
Background: Patient safety is an important discipline for improving the quality of hospital health services. By establishing a positive patient safety culture in a hospital, the commitment to create a safer patient safety culture as an act to reduce incidents is also higher. One of the supporting factors of patient safety culture is teamwork. Teamwork is an effort to work with other people cooperatively as a part of the group. Hospital